Alkyl-group-wrapped unsymmetrical squaraine dyes for dye-sensitized solar cells: branched alkyl chains modulate the aggregation of dyes and charge recombination processes - Singh, Ambarish Kumar; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2020)
Electron transfer processes at the interfaces dictate the factors that improve the photovoltaic parameters, such as open-circuit voltage (V-oc) and short-circuit current (J(sc)), of a dye-sensitized solar cell device, besides selection of a set of suitable anode, dye, electrolyte, and cathode materials. An inefficient charge injection process at the dye-TiO2 interface and charge recombination at the TiO2-dye/electrolyte interface have detrimental effects on improving both J(sc) and V-oc. Hence, tailoring the factors that govern the improvement of J(sc) and V-oc will be an ideal approach to get the desired sensitizers with good device efficiencies. Squaraines are far-red-active zwitterionic dyes and have a high molar extinction coefficient along with unique aggregation properties due to the large dipole moment associated with them. Here, we report a series of unsymmetrical squaraine dyes, SQS1 to SQS6, with systematic variation of alkyl groups at the sp(3)-C and N-atoms of the indoline unit that is away from the anchoring group to control the dye-dye interactions on the TiO2 surface. The branched alkyl groups help in modulating the self-assembly of sensitizers on the TiO2 surface, besides passivating the surface that helps avoid the charge recombination processes. Light harvesting efficiency and cyclic voltammetry studies of dye-sensitized TiO2 electrodes indicate that the aggregation and charge hopping process between the dye molecules can be modulated, respectively, by systematically increasing the number of carbon atoms in the alkyl groups. Such a variation in the branched alkyl group helps enhance V-oc from 672 (SQS1) to 718 mV (SQS6) and J(sc) from 7.95 (SQS1) to 12.22 mA/cm(2) (SQS6), with the device efficiency ranging from 3.82% to 6.23% without any coadsorbent. Dye SQS4 achieves the highest efficiency of 7.1% (V-oc = 715 mV, J(sc) = 13.05 mA/cm(2)) with coadsorbent chenodeoxycholic acid (CDCA) using an iodine (I-/I-3(-)) electrolyte compared to its analogues. An analysis of the incident photon-to-current efficiency profiles indicates that the major contribution to photocurrent generation is from the aggregated squaraine dyes on TiO2.
Keywords: aggregation of dye; charge injection; charge recombination; Dye-sensitized solar cells; unsymmetrical squaraines